Capitec Bank : low-cost banking for Joe Average - Townsend, Stephanie; Mosala, Thabo ([London] : SAGE, 2016)
By December 2006, Capitec Bank, South Africa's newest listed retail bank, had come a long way from its origins as a microlending organisation in 2001. Over time it had started introducing other banking services to its entry-level clients, so that by 2006 it offered all basic banking services. However, Capitec's chief executive for marketing and corporate affairs, Carl Fischer, realised that the key to survival for a low-cost bank in South Africa lay in high volumes. This book examines how Capitec overcame perceptions that it was a niche bank in order to attract the volumes it needed to prosper.
Originally Published in: Townsend, S., & Mosala, T. (2006). Capitec Bank: Low-Cost Banking for Joe Average. WBS-2006-21. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Capitec Bank (Firm); Corporations -- Growth -- Case studies; Bank marketing -- Case studies; Marketing -- Case studies